Incidence of insect pests (rice bugs) and their natural enemies in selected rice (Oryza sativa) paddies in Villareal, Samar - Rado, Regine Pearl B.; Parilla, Richard B. (2022)
Rice is considered as the most important agricultural crop in the Philippines. It serves not only as a food source, but also as a major source of income for the farmers and the economy. Furthermore, rice bugs are major pests in rice crop ecosystems, causing grain damage and yield loss. Rice bug infestation is a major problem in the rice fields in Villareal, Samar. The pests and their natural enemies were captured through hand collection and sweeping methods in 15 rice paddies of 5 m x 5 m area to monitor their incidence throughout a five-wek sampling period. Across all three surveyed barangays, a total of three rice bug species (Leptocorisa acuta, Riptortus linearis, and Scotinophara sp.) were documented, with L. acuta as the most abundant in all rice fields. The abundance was mostly credited to rice growth stages, with the highest during flowering and milk and dough stages. A total of 10 species of natural enemies were recorded, which included beetles, spiders, dragonfly, damselfly, and fly belonging to nine families. The most common were Micraspis discolor (rice red ladybird) and species of spiders. The rice bugs showed low species diversity and evenness and low relative abundance compared to their natural enemies which were attributed to non-usage of pesticides and predator-prey interactions, respectively. It was also identified that the incidenceof rice bugs and their natural enemies in the rice crop ecosystems had moderate (r=0.48 in Barangay Tayud, r=0.70 in Barangay Canmucat) and strong (r=0.78 in Barangay Nagcaduha) positive correlations. Due to the adverse health and environmental effects of pesticide-use, utilizing natural enemies to control these insect pests.
Undergraduate thesis (B. S. in Biology) -- University of the Philippines, Tacloban.